2020
DOI: 10.1021/acs.chemmater.9b04471
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Group IV Allotropes and Solid Solutions: Nanoparticles and Nanowires

Abstract: In the past decades, group IV nanowires and nanoparticles have been the subject of extensive research. Beside tremendous progress in morphological control and integration in advanced device architectures, research on allotropes and metastable compositions has gained considerable interest. Several new approaches now allow the controlled formation of specific allotropes in the nanostructured form as well as chemical compositions not attainable by traditional synthesis protocols. The conditions applied to form th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 594 publications
0
28
0
Order By: Relevance
“…However, recent works argued that so far pure hexagonal-diamond C crystals might not have been obtained [12,13] and that the observed materials most likely correspond to high stacking disorder in cubic diamonds (3C in the Ramsdell notation) [12][13][14]. Instead, in the case of Si and Ge, it has been recently undeniably proved that 2H-nanowires (NWs) can be grown following different approaches [15] such as crystal transfer methods [2,[16][17][18], strain and photo-induced transformation processes [19][20][21] and plasma assisted vapor liquid-solid growth [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent works argued that so far pure hexagonal-diamond C crystals might not have been obtained [12,13] and that the observed materials most likely correspond to high stacking disorder in cubic diamonds (3C in the Ramsdell notation) [12][13][14]. Instead, in the case of Si and Ge, it has been recently undeniably proved that 2H-nanowires (NWs) can be grown following different approaches [15] such as crystal transfer methods [2,[16][17][18], strain and photo-induced transformation processes [19][20][21] and plasma assisted vapor liquid-solid growth [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas synthesis methods are progressing towards the growth of extended hexagonal-type structures [15], 2H and 3C domains still coexist within a sub-micrometric scale in current samples. Furthermore, twin boundaries and more extended stacking faults in diamond-like crys-tals are hexagonal crystal inclusions with a thickness of only few atomic planes.…”
Section: Introductionmentioning
confidence: 99%
“… 30 , 31 Growth methods and critical growth constraints for the growth of Ge 1– x Sn x nanowires are detailed in a couple of recent reviews. 32 , 33 However, in most of these growth methods, Sn incorporation in the alloy nanowire is limited to below 10 atom %. In a significant development, Seifner et al reported the synthesis of high Sn content Ge 1– x Sn x nanowires ( x ≈ 0.19) via a chemical vapor deposition approach.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum confinement effect was evidenced in small Ge and GeSi NCs 16 – 18 , enabling bandgap engineering along with composition 19 , shape 20 and strain 21 , 22 leading to tuning of optical and photoelectrical properties of NCs.…”
Section: Introductionmentioning
confidence: 99%